ОСОБЛИВОСТІ РЕКОНФІГУРАЦІЇ ТРАНСФОРМАТОРНО-КЛЮЧОВОЇ ВИКОНАВЧОЇ СТРУКТУРИ СТАБІЛІЗАТОРА-РЕГУЛЯТОРА НАПРУГИ ЗМІННОГО СТРУМУ - Липківський, К.О. (Інститут електродинаміки НАН України, Київ, 2017)
Transforming elements with sectioning of windings are components of transformer-and-switches executive structures (TSES) of AC voltage converters, to which are inherent in the multivariance of circuit and algorithmic solutions. The basic TSES of stabilizer with regulation of the stabilized voltage level is proposed. Reconfiguration of this structure allows to purposefully change the limits of regulation of these levels. Several variants of such reconfiguration are considered. The expedient law of sectioning the turns of the TSES autotransformer is determined, which does not change during reconfiguration. Also, the algorithm of discrete-time control of switch elements remains unchanged. References 11, table 1, figures 4.